Pemasaran Digital dan Web dalam Rangka Meningkatkan Kunjungan ke Desa Wisata Lamajang Pangalengan - Junipriansa, Donni; Nafrila, Inez; Winantya, Beata; Humaida, Sonia; Harsya Sadin, Muhamad; Lanang Ary Wisana, I Made; Dewi Puspita, Widya; Luthfiyah, Hasna; Samdya Putra, Faisa; Aryakumara, Ganendra; Ustine Yunisa Hasibuan, Putri (LPPM Politeknik Piksi Ganesha, 2024)
Lamajang Village is a rural settlement located within the Pangalengan region of West Java. The community exhibits promising potential for natural resource-based tourism, encompassing activities such as white water rafting, historical landmarks, museums, and cultural heritage sites. In addition to the aforementioned aspects, this hamlet offers a diverse range of traditional cuisine and gastronomic delights, with a variety of artisanal products. Nevertheless, the village in question has failed to achieve its full potential as a premier tourist destination due to its limited marketing capabilities, particularly in effectively promoting itself as an attractive location for tourists. Consequently, the number of visitors to this tourist hamlet remains relatively low. Hence, it is imperative to conduct outreach and training initiatives pertaining to digital marketing, website development, and tour package management. The event is scheduled to occur on October 8, 2023, with the intention of inviting a total of 30 people from Lamajang tourist Village. The findings of the study indicate that there is a favourable reception from various stakeholders, including the village head, public, tourism actors, and MSMEs. The continuation of this programme is expected to make a significant contribution to the growth of Lamajang Tourism Village